Childhood overweight and obesity management: A national perspective of primary health care providers’ views, practices, perceived barriers and needs - He, Meizi (Pulsus Group Inc, 2010)
BACKGROUND: Obesity and overweight in children are an escalating problem in Canada and worldwide. Currently, little is known about the manner in which primary health care providers are responding to Canada’s obesity epidemic. OBJECTIVE: To determine the views, practices, challenges/barriers, and needs of a national sample of family physicians (FPs) and community paediatricians (CPs) with respect to paediatric obesity identification and management. METHODS: A self-administered questionnaire was mailed to a random sample of 1200 FPs and 1200 CPs across Canada between 2005 and 2006. RESULTS: A total of 464 FPs and 396 CPs participated. The majority of practitioners viewed paediatric obesity as an ‘important’/‘very important’ issue. Although the majority reported providing dietary (more than 85%) and exercise (98%) advice to their overweight/obese patients, practitioners’ perceived success rate in treating paediatric obesity was limited (less than 22%). Approximately 30% of FPs and 60% of CPs (P<0.05) used the recommended method to identify paediatric obesity. At least 50% of practitioners indicated that too few government-funded dietitians, a lack of success in controlling paediatric patients’ weight, time constraints and limited training were key barriers to their success. To support efforts to identify or manage paediatric obesity, practitioners identified the need for office tools, patient educational materials and system-level changes. DISCUSSION: Canadian primary health care providers are not adequately equipped to deal with the paediatric obesity epidemic. Effective assessment tools and treatment resources, dissemination of clinical practice guidelines, enhanced undergraduate medical education and postgraduate continuing medical education, and system-level changes are urgently needed to address this health problem.